2017
DOI: 10.1080/10942912.2017.1315590
|View full text |Cite
|
Sign up to set email alerts
|

Comparative characterization of volatile profiles of French, Italian, Spanish, and Polish red wines using headspace solid-phase microextraction/gas chromatography-mass spectrometry

Abstract: The aim of the study was to investigate whether the wines produced in France, Italy, Spain, and Poland differ in composition of volatile compounds, and whether red wines from Poland can be distinguished from those of other European countries. Thirty-five aroma compounds belonging to several groups -13 alcohols, 9 acids, 3 aldehydes, 7 esters, 2 ketones, and 1 volatile phenolwere identified in the examined wines. The proportions of volatile compounds in wines from the four selected countries were similar. Stati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
2
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 34 publications
(15 reference statements)
1
12
2
3
Order By: Relevance
“…Increases in acetate esters in wine samples have been observed during the ageing of wines or remained stable, these findings being in agreement with other studies [54,55]. Among ethyl esters, the most abundant compounds in wines samples were ethyl hexanoate, ethyl decanoate, and ethyl lactate, the same findings were reported for Italian wines, Spanish wines, Polish wines and French wines [48].…”
Section: Esterssupporting
confidence: 91%
See 2 more Smart Citations
“…Increases in acetate esters in wine samples have been observed during the ageing of wines or remained stable, these findings being in agreement with other studies [54,55]. Among ethyl esters, the most abundant compounds in wines samples were ethyl hexanoate, ethyl decanoate, and ethyl lactate, the same findings were reported for Italian wines, Spanish wines, Polish wines and French wines [48].…”
Section: Esterssupporting
confidence: 91%
“…The content of higher alcohols of wines aged for 12 months was ranged from 6878.20 µg/L (Fetească Neagră from the south-east region) to 22515.33 µg/L (from Cabernet Sauvignon from the north-west region) being 9.74% and 32.66% respectively, for volatiles detected at this stage ( Table 3). The concentrations of alcohols of the total volatile compounds in wines from our study were much lower compared with those reported in French wines 44 [48].…”
Section: Alcoholscontrasting
confidence: 89%
See 1 more Smart Citation
“…Volatiles can also be created by yeast fermentation, mainly during wine, beer, and bread making [ 116 ]. Research carried out by Makhoul and co-workers focused on the production of VOCs during fermentation with the use of three commercial S. cerevisiae strains.…”
Section: Sensory Profile: Impact Of Volatile Organic Compounds On mentioning
confidence: 99%
“…These results indicate that a 'volatile fingerprint' of PKE (low and high-water content) and PKM (solvent extraction) can be established based on the processing technology and geographical origin of samples. Comparative study on volatile profiles of plant-based products like wine, olive oil and honey have been carried out to understand the contribution of geographical origin, processing technology, and other variables on the products to establish criteria of product quality (da Costa et al, 2018;Stój et al, 2017;Tura et al, 2004). Our study on volatile profiles of PKE and PKM would allow localization of these products based on their quality and provide a basis for customization of feed to improve palatability.…”
Section: Classification and Data Analytics Of Volatiles For Pke And Pkmmentioning
confidence: 99%